Freedom as Virus: A Critique of the Neoliberal Notion of Freedom and an Analysis of its Cultural Consequences - Aaron Michael Mulligan (INSAM)
The extent to which the COVID pandemic has been shaped by communication is enigmatic as the very term “viral” has become a term of information science as much as of biology. Insofar as sizable populations have become cynical about information regarding COVID, their behavior has accelerated the threat of the virus. This paper proposes that this pandemic is fundamentally a crisis of communication emerging from antagonisms and inconsistencies latent within a general concept of “freedom”. The notion of freedom that has emerged with neoliberalism is one of a lack of regulation. Such a naive idea of freedom becomes particularly problematic when compounded with the classical liberal value of freedom of speech. This paper addresses the impossibility of unlimited speech, particularly on the internet, focusing on the desire such impossibility stimulates. This desire is an economic fuel for social media platforms. Insofar as artists share their practices via social media and generally use these platforms for networking, their practices inherit contradictions that artists must become conscious of to prevent a web-based practice from becoming emotionally exploitive and economically complicit. This crisis amplifies those contradictions that drive the artist to the point of despair.